Methods of functional and process accounting of environmental costs - Sotnikova L. V., Gerasimova L. N., Polenova S. N., Mislavskaya N. A., (Opción, 2019)
The article discusses issues related to environmental protection of a number of construction companies, reveals the essence of environmental protection costs, as well as the need to form an active environmental strategy and its implementation via the scientific apparatus of management accounting, standard methods of analysis and evaluation. As a result, economic entities must independently identify the qualifying features of environmental protection costs and their functional capabilities. In conclusion, improper organization, work and ill-conceived technologies entail enormous costs of materials and energy and lead to severe pollution of the natural environment.